Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
-147*47+(-47)*(-47)-300
\(=-47.\left(147+1-300\right)\)
\(=-47.\left(-152\right)\)
\(=7144\)
học tốt
-147.47+(-47).(-47)-300
=-47.(147-47)-300
=-47.100-300
=-4700-300
=-5000
(-147).13-13.(-47)
=13.(-147+47)
=13.(-100)=-1300
chọn mink nha!!!
( - 13 ) + 147 + 13 + ( - 47 )
= ( 13 - 13 ) + ( 147 - 47 )
= 0 + 100
= 100
( - 13 ) + 147 + 13 + ( -47 )
= [ ( -13 ) + 13 ] + [ 147 + ( - 47 ) ]
= 0 + 100
= 100
d) 135(-12 + 247) - 147(135 - 12)= -12.135 + 135.147 - 147.135 + 12.147 = (-12.135 + 12.147) + (135.147 - 147.135) = 12(-135 + 147) + 0 = -12.12 = -144
Bài 1:
a) [3.(-2) - (-8)].(-7) - (-2).(-5) = -7(-6 + 8) - 2.5= -7.2 - 2.5 = -2(7 + 5) = -2.12 = -24
a) 47.(-147) - 47.(-47)
= 47.(-147 + 47)
= 47 . (-100)
= -4700
b) 24.(15 - 4) + 4.(24 - 15)
= 24.15 - 25.4 + 4.25 - 4.15
= (24 - 4).15 - (25.4 - 4.25)
= 20 . 15
= 300
Sửa lại đầu bài nha bạn :
-25 ( 35 + 47 ) + 35 ( 25 + 47 )
= - 25 x 35 + ( -25 ) x 47 + 35 x 25 + 35 x 47
= [ -25 x 35 + 35 x 25 ] + [ -25 x 47 + 35 x 47]
= 0 + [ ( -25 + 35 ) x 47 ]
= 0 + 10 x 47
= 470
-25. (35+47)+35.(25+147)
= (-25).35+(-25).47+35.25+35.147
= [(-25).35+35.25]+[(-25).47+35.147]
= 0 + [(-1175)+5145]
= 0 + 3970
= 3970
a) -(275-147)-(47-275)
= −128−(47−275)
= −128−(−228)
= 100
Vậy -(275-147)-(47-275)=100
2x + 47 = 147
2x = 147 - 47
2x = 100
x = 100 : 2
x= 50
Vậy x=50
_HT_